2006
DOI: 10.1353/psc.2006.0033
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizae Effects on Growth of Two Hawaiian Species: Indigenous Osteomeles anthyllidifolia (Rosaceae) and Invasive Psidium cattleianum (Myrtaceae)

Abstract: Two important plant species of Hawai'i, the indigenous Osteomeles anthyllidifolia (Sm.) Lindl., a component of Hawai'i's most endangered habitat, and the highly invasive Psidium cattleianum Sabine were grown with or without arbuscular mycorrhizal fungi in a soilless mix at different soil-solution phosphorus (P) levels. At P levels similar to those in the field (0.007 mg P/liter), shoot biomass of inoculated plants of O. anthyllidifolia was 189% greater than that of controls, and that of P. cattleianum was 93% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…Osteomeles anthyllidifolia (Rosaceae), inoculated with six AMF species simultaneously, achieved values of mycorrhizal dependency between 46% and 76%. Nevertheless, these values were related to P content in soils, being higher in soils with lower P content [ 46 ]. In the case of representatives of Asteraceae, mycorrhizal dependency of R .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteomeles anthyllidifolia (Rosaceae), inoculated with six AMF species simultaneously, achieved values of mycorrhizal dependency between 46% and 76%. Nevertheless, these values were related to P content in soils, being higher in soils with lower P content [ 46 ]. In the case of representatives of Asteraceae, mycorrhizal dependency of R .…”
Section: Discussionmentioning
confidence: 99%
“…However, ecologists also signalise that since AMF show functional diversity and their effects are within mutualism and parasitism spectrum [ 51 53 ], the key point is to select single effective AMF species than focus on species richness [ 54 ]. No without significance in plant-AMF relationships are also other factors, like soil physical and chemical properties [ 46 , 47 , 55 ] as well as presence of biotic and abiotic stresses. It was reported that AMF can have positive effects on plants in the presence of stressors, such as salinity and heavy metal toxicity [ 56 – 59 ], by both nutritional and non-nutritional mechanisms [ 57 , 58 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Colonization of endemic plants by AM fungi has also been reported in Hawaii and the Galapagos, although the molecular diversity was not characterized (Schmidt & Scow, 1986;Koske & Gemma, 1996;Gemma et al, 2002). Although we have not studied the function of these mycorrhizal fungi in the Canary Islands, native mycorrhizas in Hawaii more than doubled the biomass and phosphorus uptake of a native shrub found in endangered dry forest habitat in Hawaii (Koske & Gemma, 2006). Thus, island mycorrhizas warrant further study in the context of plant conservation and management.…”
Section: Discussionmentioning
confidence: 88%
“…Many previous studies concerning invasion by non-native plant species were focused on aboveground features with little attention given to belowground soil organisms (Levine et al 2004 ; Pyšek and Jarošík 2005 ; Sala et al 2000 ; Vitousek et al 1996 ). A few recent studies demonstrated the role of AM in plant invasion however most of studies focused on greenhouse, pot or microcosm experiments not on field studies (Koske and Gemma 2006 ; Richardson et al 2000 ; Štajerová et al 2009 ; Stampe and Daehler 2003 ). Root endophytes like AMF and DSE are common colonizers of plant roots across wide range of habitats (Kauppinen et al 2014 ; Mandyam and Jumpponen 2005 ; Smith and Read 2008 ).…”
Section: Introductionmentioning
confidence: 99%